Lower lip depressor reanimation using anterior belly of digastric muscle transfer improves psychological wellbeing in facial palsy patients. Issue 3 (April 2022) - Mabvuure, Nigel Tapiwa; Pinto-Lopes, Rui; Bolton, Lauren; Tzafetta, Kallirroi
Abstract: The authors previously published positive peer-reviewed (21 raters using the Terzis scale) and photogrammetric (Emotrics) outcomes in patients who had undergone two-stage lower lip reanimations up to 2018. Other series have published surgeon and peer-rated results, but we know of only two (n=12) that have assessed patients' views using patient satisfaction surveys. This paper presents patient-rated outcomes (PROMS) in an 11-year series of both single and two-stage anterior belly of digastric muscle (ABDM) lower lip reanimations. Demographics, paralysis characteristics, operative details, and complications were recorded. Patients were telephoned and requested to complete the Glasgow Benefit Inventory (GBI) to assess patient-rated outcomes. Thirty-two patients were eligible (mean age 36.4 years). Twenty-one (63.6%) completed the GBI (mean score +33.3). More patients reported benefit than detriment (95.2% vs 4.8%). Complications were infrequent and included three cases of superficial infections and one of dermatitis. Four patients (12.5%) underwent minor revisions, mostly lipofilling of lip notches. The median (range) duration of follow up was 2.8 (0.3 – 8.5) years. ABDM transfer for lower lip reanimation is a safe, low morbidity procedure that enhances the psychological wellbeing of patients with facial palsy.